A Synthesis of the Ramsey-Meade Problems when Population Change is Endogenous - Lane, John S. (Review of Economic Studies, 1975)
Journal Article A Synthesis of the Ramsey-Meade Problems when Population Change is Endogenous Get access John S. Lane John S. Lane London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 1, January 1975, Pages 57–66, https://doi.org/10.2307/2296819 Published: 01 January 1975